2022
DOI: 10.1029/2022jc018877
|View full text |Cite
|
Sign up to set email alerts
|

Density Staircases Are Disappearing in the Canada Basin of the Arctic Ocean

Abstract: In the Canada Basin of the Arctic Ocean, warm and salty Atlantic‐origin Water (AW) lies in the intermediate layer (250–800 m) below a colder and fresher surface layer. It results in a depth range where vertical thermohaline gradients are propitious to double‐diffusion. Indeed, thermohaline staircases are commonly observed and associated with double‐diffusive processes. Using observations from the Beaufort Gyre Exploration Project large database and Ice‐Tethered Profilers, we document the presence of density st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…These structures have been observed throughout the world’s oceans (van der Boog et al, 2021a) as well as in saline lakes (Newman, 1976), while related double-diffusive staircases are thought to occur in gas giants such as Jupiter and Saturn (André et al, 2017; Pontin et al, 2021). In particular, they are well known to occur in the Arctic Ocean (Timmermans et al, 2008; Lu et al, 2022; Ménesguen et al, 2022). Around 250 to 800 meters below the surface of the Arctic Ocean, there is a layer of water originating from the Atlantic, which is warmer and saltier than the topmost layer that is in contact with the sea ice above (Timmermans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures have been observed throughout the world’s oceans (van der Boog et al, 2021a) as well as in saline lakes (Newman, 1976), while related double-diffusive staircases are thought to occur in gas giants such as Jupiter and Saturn (André et al, 2017; Pontin et al, 2021). In particular, they are well known to occur in the Arctic Ocean (Timmermans et al, 2008; Lu et al, 2022; Ménesguen et al, 2022). Around 250 to 800 meters below the surface of the Arctic Ocean, there is a layer of water originating from the Atlantic, which is warmer and saltier than the topmost layer that is in contact with the sea ice above (Timmermans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While Arctic sea ice has been steadily disappearing (Comiso et al, 2008), the density stratification above the AW core has historically been strong enough to insulate surface waters from the warmth at depth (Shibley et al, 2017). However, the lower sections of Arctic staircases have been disappearing in recent years (Ménesguen et al, 2022). Many works have noted that the AW contains enough heat to melt all Arctic sea ice, if it were somehow able to reach the surface (Maykut and Untersteiner, 1971; Turner, 2010; Stranne et al, 2017; Shibley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These structures have been observed throughout the world's oceans [50] as well as in saline lakes [29], while related double-diffusive staircases are thought to occur in gas giants such as Jupiter and Saturn [1,34]. In particular, they are well known to occur in the Arctic Ocean [47,17,23]. Around 250 to 800 meters below the surface of the Arctic Ocean, there is a layer of water originating from the Atlantic, which is warmer and saltier than the topmost layer that is in contact with the sea ice above [47].…”
Section: Introductionmentioning
confidence: 99%
“…While Arctic sea ice has been steadily disappearing [6], the density stratification above the AW core has historically been strong enough to insulate surface waters from the warmth at depth [41]. However, the lower sections of Arctic staircases have been disappearing in recent years [23]. Many works have noted that the AW contains enough heat to melt all Arctic sea ice, if it were somehow able to reach the surface [19,49,45,42].…”
Section: Introductionmentioning
confidence: 99%
“…It is energetically quiescent in the Arctic Ocean's central basins [11]. Ménesguen et al reported that the DC staircases gradually vanished in the Canada Basin [12]. Mclaughlin et al proposed that the thermohaline intrusions in AW show signs of dissipation near the Northwind Ridge, which indicated that, as temperature gradients decrease, they will disappear from the Canada Basin [13].…”
Section: Introductionmentioning
confidence: 99%